Religious Medals in Lithuanian Archaeological Material: Chronology, Distribution, Typology - Juzėnaitė, Ugnė (Vilnius University Open Series, 2024)
The subject of this research paper is religious medals in Lithuanian archeological material that had been found during archeological excavations in Lithuania during the period of 2009–2019. The abundance and variety of religious medals found during archeological excavations as of yet has not been studied. In general, the extent and diversity of these finds in museum collections has not yet been systematically assessed. The main methodological problem that derived this research to be done is the lack of papers written about this subject not only in the field of archeology but in other fields of research as well. There is only a small number of articles analyzing religious medals. This archeological material is a little-known source of history of Lithuanian culture, and systematized data on these findings would be useful for archeologists to date and describe other findings found during the archeological excavations. The main goals of this research paper are to introduce the historical evolution of religious medals; determine main finding sites of religious medals in Lithuania; determine main types of religious medals, found during archeological excavations in Lithuania; analyze and interpret religious medals found in Lithuania; determine their prevalence and development. The main findings of this research. A total of 241 religious medals have been analyzed in this study, that are kept in several different museums in Lithuania. Due to the rapidly increasing amount of this kind of archeological material available for research, it can be concluded that there is a great potential for further study into religious medals. The first religious medals were made for the miraculous paintings of the Virgin Mary. Religious medals began to be produced in Rome, Italy, and spread successfully around the world and prevailed in the Christian Europe. During archeological excavations, religious medals are found in cemeteries in churches and near them (11 sites), in burials of old cemeteries – 12 sites, in church and monastery complexes (where religious medals had been found in burials in the territory of monasteries) – 3 sites, and residential type sites (where medals had been found outside of burials) – 51 sites. A total of 77 sites were analyzed in this research. In the typology, religious medals have been grouped into 7 main types: medals of Jesus Christ; medals of the St. Virgin Mary; medals of Holy Orders; medals of Saints; medals of Sobriety fraternities; medals of monograms and “non-specific” medals. These types, if needed, were then broken down into smaller subtypes. The majority of religious medals in this research are of 19th century – 52, of 17th century – 24, 18th century – 24, 18th–19th century – 5, 19th–20th century – 32, 20th century – 9. The earliest ones, found in Lithuania, are from the year of 1625. Religious medals were made using two types of technology – they were minted or cast. Mostly made of copper alloy. There are known medals made in Lithuania of Lithuanian goldsmiths and there are known imported medals from Russia (17th–18th/19th centuries), Italy (17th–18th centuries), Spain (17th–18th centuries), Austria (18th– 19th centuries) and Poland (19th–20th centuries). The highest number of medals were found in burials near churches, least – in city’s cultural layers.